An inquiry into ethnomathematics within the framework of the traditional game of Congklak - Khasanah, Mirsatun; Khalil, Ibrahim Alhussain; Prahmana, Rully Charitas Indra (Universitas Papua, 2023)
Ethnomathematics represents a paradigm within mathematics education that centers on integrating and applying mathematical principles, concepts, and methodologies embedded within the cultural fabric of specific communities. Within the Indonesian cultural milieu, traditional games constitute a significant aspect. Hence, this study investigates the traditional game of Congklak, aiming to explicate its underlying modulo concept. Employing a qualitative research design grounded in ethnographic methodology, the investigation draws upon a multifaceted approach, including a literature review, documentation analysis, participant observation, and interviews with custodians of the Congklak tradition. Data validation is achieved through triangulation of sources and methods. Data analysis involves iterative data reduction, presentation, and inference drawing processes. Findings reveal the presence of a modulo concept within the traditional Congklak game, which governs the determination of the final seed distribution position. Furthermore, additional mathematical elements, notably addition operations, are identified. The identified modulo concept offers a compelling avenue for enriching mathematical pedagogy, particularly in the realm of modulo arithmetic operations, by providing an alternative cultural context for learning.